Spontaneous activity in the microvasculature of visceral organs: role of pericytes and voltage‐dependent Ca2+ channels. (6th January 2016) - Hashitani, Hikaru; Lang, Richard J.
Abstract : Pericytes play different roles in different microcirculatory beds In the bladder suburothelium (left), 'non contractile' capillary pericytes (CPCs) may generate 'spreading' excitation to drive venular pericytes (VPCs; upper). Excitation of VPCs upon the opening of L‐type voltage‐dependent Ca 2+ channels (LVDCCs) spread within a VPC network to generate 'peristaltic' vasoconstrictions (middle). Contractions of VPCs also work against stretching during storage phase to prevent venular collapse (lower). In the myenteric layer of the stomach (right), 'non contractile' CPCs generate 'spreading' excitation upon the opening of T‐type voltage‐dependent Ca 2+ channels (TVDCCs) to drive smooth muscle cells (SMCs; upper). Excitation of SMCs upon the opening of TVDCCs spread within a SMC network to generate 'synchronous' vasoconstrictions (lower). Cells in red indicate excited and contracted. Cells in light blue indicate in resting state. Cells in orange indicate excited but non‐contractile. Abstract: The microvasculature plays a primary role in the interchange of substances between tissues and the circulation. In visceral organs that undergo considerable distension upon filling, the microvasculature appears to display intrinsic contractile properties to maintain their flow. Submucosal venules in the bladder or gastrointestinal tract generate rhythmic spontaneous phasic constrictions and associated Ca 2+ transients. These events are initiated within either venular pericytes or smooth muscle cells (SMCs) arising from spontaneous Ca 2+ release from the sarcoplasmic reticulum (SR) and the opening of Ca 2+ ‐activated chloride channels (CaCCs) that trigger Ca 2+ influx through L‐type voltage‐dependent Ca 2+ channels (VDCCs). L‐type VDCCs also play a critical role in maintaining synchrony within the contractile mural cells. In the stomach myenteric layer, spontaneous Ca 2+ transients originating in capillary pericytes appear to spread to their neighbouring arteriolar SMCs. Capillary Ca 2+ transients primarily rely on SR Ca 2+ release, but also require Ca 2+ influx through T‐type VDCCs for their synchrony. The opening of T‐type VDCCs also contribute to the propagation of Ca 2+ transients into SMCs. In visceral microvasculature, pericytes act as either spontaneously active contractile machinery of the venules or as pacemaker cells generating synchronous Ca 2+ transients that drive spontaneous contractions in upstream arterioles. Thus pericytes play different roles in different vascular beds in a manner that may well depend on the selective expression of T‐type and L‐type Ca 2+ channels.